Desain Transmisi Hidrostatik untuk Roda Penggerak pada Mobil Terbang - Faiz Akbar Pradipta; Mohammad Adhitya (Universitas Muhammadiyah Yogyakarta, 2024)
A flying car can fulfill two functions, as a vehicle on the road and as an airplane that capable of flying. To reduce aerodynamic drag, the drive wheels must be able to fold so that a flexible transmission system is required. The Hydrostatic Transmission (HT) system is a flexible transmission that uses a hose to connect hydraulic pump, which is coupled to the engine, to hydraulic motor, which is coupled to the wheel. This research analyzes the specifications of hydrostatic transmission components to optimally transmit power from a V6 engine to two drive wheels through a speed gear transmission system. The hydrostatic transmission system specifications, which include pumps, motors, hoses, charge pumps, and release valves, are analyzed using Simscape MATLAB software. This software enables the user to easily modify the parameters to build an optimal hydrostatic transmission design. To ensure optimal performance of the entire flying car propulsion system, a 60kW pump and 20kW motor are required.